1999
DOI: 10.1046/j.1365-246x.1999.00927.x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the crustal structure in southern Tibet by dispersion and amplitude analysis of Rayleigh waves

Abstract: Summary Surface waves recorded by the nine broad‐band stations of the INDEPTH II experiment are analysed to study the crustal structure of southern Tibet. Their frequency range is between approximately 0.015 and 0.050 Hz (i.e. between 20 and 60 s period). Phase velocity dispersion curves are calculated for the regions north and south of the Tsangpo suture, using Wiener filtering of fundamental mode Rayleigh waves incident upon the array with different backazimuths. The two dispersion curves are inverted to obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
48
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 30 publications
8
48
0
Order By: Relevance
“…7) throughout the mid-crust in most of Tibet has also been observed in a number of previous studies (e.g. Cotte et al 1999;Rapine et al 2003;Caldwell et al 2009;Guo et al 2009;Li et al 2009;Yang et al 2012;Agius & Lebedev 2014;Jiang et al 2014;Li et al 2014;Sun et al 2014;Bao et al 2015;Deng et al 2015;Gilligan et al 2015). Our results have high resolution across the entire Tibetan Plateau and the Pamirs, whereas many previous studies have mainly focused on more restricted geographical regions.…”
Section: P O S S I B L E C Au S E O F T H E L O W V E L O C I T Y L Asupporting
confidence: 85%
“…7) throughout the mid-crust in most of Tibet has also been observed in a number of previous studies (e.g. Cotte et al 1999;Rapine et al 2003;Caldwell et al 2009;Guo et al 2009;Li et al 2009;Yang et al 2012;Agius & Lebedev 2014;Jiang et al 2014;Li et al 2014;Sun et al 2014;Bao et al 2015;Deng et al 2015;Gilligan et al 2015). Our results have high resolution across the entire Tibetan Plateau and the Pamirs, whereas many previous studies have mainly focused on more restricted geographical regions.…”
Section: P O S S I B L E C Au S E O F T H E L O W V E L O C I T Y L Asupporting
confidence: 85%
“…Although previous geophysical observations (e.g., Nelson et al, 1996) and the results of geodynamic modeling (e.g., Beaumont et al, 2001Beaumont et al, , 2006 suggest that channel flow may occur at depths of 20-30 km beneath southern Tibet (i.e., mid-crustal levels), other recent studies suggest that channel flow may also occur in the lower crust, as indicated by widespread high-conductivity layers in the mid-lower crust (e.g., Jin et al, 2010;Wei et al, 2010), a pronounced low-velocity channel that extends from 30 to 70 km depth in the mid-lower crust (e.g., Cotte et al, 1999), and the fact that earthquakes are absent at depths of 30-65 km beneath the Lhasa terrane (e.g., Chen and Yang, 2004;Jackson 2002aJackson , 2002bJackson et al, 2004). These findings imply that mid-lower crustal material beneath Southern Tibet is ductile and therefore may take place ductile flow.…”
Section: Southeastward Ductile Flow Of the Mid-lower Crust Beneath Wementioning
confidence: 98%
“…Since the 1980s, many Chinese and foreign seismologists have studied the crust and upper mantle structure of the Tibetan Plateau by using seismic body wave and surface wave data [5][6][7][8][9][10][11][12][13][14][15][16][17][18] , and have studied the upper mantle anisotropy beneath the Tibetan Plateau using teleseismic SKS-wave splitting [19][20][21][22][23][24][25][26][27][28] . Hirn et al [20] considered seismic anisotropy as an indicator of mantle flow beneath Himalayas and Tibet, and they thought that the anisotropy of the Plateau is caused by the re-orientation of crystal lattice or the oriented arrangement of liquid-filled cracks due to differential shear deformation in the horizontal plane.…”
mentioning
confidence: 99%